Prenatal echographic diagnosis of phocomelia in the upper limbs - Acelia Salmon Cruzata; Julio Ernesto Rodríguez Serret; Humberto Gómez Pérez (Centro Provincial de Información de Ciencias Médicas, 2020)
The case report of a 28 years patient is described, she was admitted to Tamara Bunke Bider Teaching Gynaecoobstetric Hospital in Santiago de Cuba at the 23.4 weeks of pregnancy with the objective of interrupting pregnancy, due to the specialists of the Provincial Center of Medical Genetics suggestion who had detected a fetal malformation (phocomelia of the upper limbs) in the echography of the second trimester. When the fetus was removed, a hysterectomy was carried out and the echographic diagnosis was confirmed.